Internalization of Entrepreneurial Character in Biology Learning through Environmental Approach - Lutfi, Lutfi; Amir, Nour Ariyanti; Irfan, Muhammad; Sahabuddin, Romansyah; Zahir, Abdul (IAIN Kendari, 2024)
This research aims to explore various approaches that have been applied in teaching biology with an environmental approach to develop students' entrepreneurial character. This article uses a systematic review method based on several references from books, articles, and online scientific publications. In conclusion, this literature review shows that environmental-based projects, collaboration with environmental organisations, and comprehensive curriculum integration can improve students' entrepreneurial skills. However, there are challenges in implementing these methods, especially regarding long-term impact evaluation and appropriate teaching strategies. Thus, this study provides insights into the importance of entrepreneurship integration in biology education to shape sustainable entrepreneurial character, and offers recommendations for further research in curriculum development that is adaptive to the needs of the times.